2003
DOI: 10.1108/14676370310485410
|View full text |Cite
|
Sign up to set email alerts
|

Science education and sustainability initiatives

Abstract: Instructors at Francis Marion University developed a recycling course in an attempt to satisfy the students’ goals of increasing campus awareness about sustainability and recycling, and the teachers’ goals of using problem‐based learning approaches in class. Students enrolled in the course designed their own experiment, completed the experiment and presented the results at several national meetings. The focal point of the experiment was student apartments, where some students were provided with recycling bins,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Recent studies on recycling have also focussed on the use of recycled aggregates in various construction activities (Cavalline and Weggel, 2013;Richardson et al, 2009;Nassar and Soroushian, 2012;Kanellopoulos et al, 2014). Concurrently, several other studies have focused on recycling behaviour among people of varying background (Ramayah and Rahbar, 2013;Bezzina and Dimech, 2011;Pike et al, 2003). Unfortunately, apart from those with limited theoretical knowledge on the subject area (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on recycling have also focussed on the use of recycled aggregates in various construction activities (Cavalline and Weggel, 2013;Richardson et al, 2009;Nassar and Soroushian, 2012;Kanellopoulos et al, 2014). Concurrently, several other studies have focused on recycling behaviour among people of varying background (Ramayah and Rahbar, 2013;Bezzina and Dimech, 2011;Pike et al, 2003). Unfortunately, apart from those with limited theoretical knowledge on the subject area (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Another study that provided students with recycling bins for their rooms showed a reduction in the students’ waste stream and an increase in the percentage of waste that was recycled [12]. Other studies have assessed students’ attitudes toward recycling on campus.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on college campuses found that increased access to recycling bins coupled with raffles and contests led to improved recycling habits among students [ 10 , 11 ]. Another study that provided students with recycling bins for their rooms showed a reduction in the students’ waste stream and an increase in the percentage of waste that was recycled [ 12 ]. Other studies have assessed students’ attitudes toward recycling on campus.…”
Section: Introductionmentioning
confidence: 99%
“…Since campuses act as both planners and developers, they face similar constraints to accessing funding and implementing new stormwater management techniques. While studies frequently examine the pro-environmental preferences of campus residents (for instance see: Attaran and Celik 2015;Whalen et al 2013;Emanuel and Adams 2011;Pike et al 2003), studies on university campuses' environmental compliance or sustainability performance are limited. Only one study, a master's thesis (Garrett 2017), directly touches on campus stormwater management.…”
Section: Environmental Regulatory Compliance Regimes and University Campus Managementmentioning
confidence: 99%